Prevalence and assoociated risk factors of intestinal parasitic infections among patients admitted to Hospital Tengku Ampuan Afzan, Kuantan, Pahang - Abdullah Asady Abdul Hamid (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Intestinal parasitic infections (IPIs) cause common health conditions among humans in the tropics. Current assessments suggest that about one third of the total world population is infected with IPIs. There is a need for more data on IPIs in the hospital setting in Malaysia. This study is aimed to determine the prevalence and associated risk factors of IPIs among patients admitted to Hospital Tengku Ampuan Afzan, Kuantan, Pahang, Malaysia. A cross sectional study was conducted among 304 subjects. A total of 155 stool specimens were examined using direct wet mount, concentration techniques: sedimentation and Kato-Katz; Harada-Mori; and special staining techniques: Trichrome and Modified Ziehl-Neelsen. Data on socio-demography and hygiene practices of the patients were collected using a pre-tested questionnaire. Results were analysed using IBM SPSS Statistics version 22. Age of the subjects ranged from below one year to 78 years old, with a median of 2 years (IQR=3); 80% of them were under the age of 6 years. Gender distribution was almost equal; and 93.5% of the study populations were Malays. The overall prevalence of IPIs was 33.5%, with higher frequency of protozoan infections (29%) as compared to helminth infections (6.5%).The most prevalent protozoan infection by far was Cryptosporidium spp. (27.1%), followed by Blastocystis spp. (3.2%), Iodamoeba butschlii and Endolimax nana (0.6% each). Intestinal helminth infection was low: the most common intestinal helminth was Ascaris lumbricoides (5.2%), followed by hookworms (1.3%) and Trichuris trichiura (0.6%). Factors significantly associated with overall IPIs using Chi-square analysis were: i) washing hands after using toilet, ii) washing hands before meals, iii) wearing footwear when going outside the home and iv) ownership of poultry. In logistics regression analysis, only poultry ownership retained its role as protective factor against IPIs. Moreover, logistic regression model confirmed the presence of blood in stool as a predictor IPIs. In conclusion, prevalence of IPIs particularly Cryptosporidium spp. was higher than expected. This could possibly be an outbreak of this infection, or the presence of a chronic higher frequency which had remained undetected. Proper measures to control the level of Cryptosporidium spp. in river and water sources for drinking and recreation, and among cattle in Kuantan can help to reduce the level of infection. The low level of intestinal helminth infection probably indicates better health practices among the public around Kuantan.